Understanding marketing and marketing policies in international markets - Hazel T. Suchard (South African Journal of Business Management, 1985)
Marketing and marketing policy in international markets, must be based, according to the authoress, upon the level of economic development within a specific country and regions within a specific country. The authoress proceeds to provide stages in development and discusses the implications for product policy, pricing policy, promotion policy, and distribution policy. The impact of other economic factors, cultural forces, political and legal forces are also discussed. The authoress concludes by referring to rural versus urban distribution and its influence on international marketing.
Keywords: 650